Recurrence of a complex anterior skull base tumour managed with an uncommon surgical approach. Issue 3 (20th March 2019) - Alvi, Muhammad Ibaad ur Rehman; Pathmanaban, Omar; Bhalla, Raj; Mani, Navin
Abstract : A well 74 -year-old woman presented to routine ophthalmology clinic instituted following treatment of a frontoethmoidal sarcoma initially excised in 1989 and diagnosed then as a sinus mucosal melanoma. At review in ophthalmology clinic, a reduction in right visual fields was noted. CT scan showed recurrence of a mass now involving the frontoethmoidal region, frontal sinus and abutting the cribiform plate. Endoscopic biopsy confirmed the recurrence as a low-grade biphenotypic sarcoma. This was discussed at the sarcoma multidisciplinary meeting. Using a three-dimensional printed model of the patients skull for planning, primary surgery with craniofacial resection combining intracranial and transfacial approaches with reconstruction was decided on. The implications of no treatment would be tumour involvement of the dura and brain as well as the right only-seeing eye. Craniofacial surgery would involve otolaryngolical, neurosurgical and maxillofacial multispecialty involvement and close teamwork. The goal was en bloc excision with negative surgical margins.